Teori ASyA (Adaptive Shariah Advantage): Studi Interdisipliner tentang Maqasid al-Shariah dan Konsep MILES dalam Merumuskan Ketahanan Masyarakat Muslim - M Yakhsyallah Liddinillah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
Contemporary Muslim societies are increasingly shaped by a pattern of ritual-centered religiosity that emphasizes symbolic devotion while neglecting the substantive objectives of Islamic law (maqasid al-shariah). This trend has generated a fragile form of social resilience, marked by weakened critical literacy, poor economic planning, deteriorating family communication, and heightened vulnerability to psychological and social pressures. This condition reflects an urgent crisis of meaning, in which religious enthusiasm is no longer balanced by strategic rationality and ethical responsibility. Classical Islamic scholarship, as represented by Al-Ghazali, Al-Shatibi, and Ibn al-Qayyim, positions maqasid al-shariah as the core of Islamic law, oriented toward the preservation of religion, life, intellect, wealth, and lineage. However, in contemporary contexts, this normative framework often remains abstract and detached from practical social realities, resulting in a persistent gap between theory and lived experience. This study aims to formulate the ASyA Theory (Adaptive Shariah Advantage) as an integrative model that reconnects maqasid al-shariah with the practical dimensions of modern life through the MILES framework (Money, Intelligence, Location, Education, Status). The research employs an original qualitative approach termed the Maqasid–MILES Adaptive Synthesis Method (MMAS), which consists of three stages: (1) textual deconstruction of classical maqasid literature, (2) logical fallacy mapping of contemporary religious discourse, and (3) critical adaptive synthesis linking maqasid domains with MILES components. The study produces an interdisciplinary conceptual matrix in which each element of MILES is systematically mapped onto the five essential protections of maqasid al-shariah. This integration offers a dynamic and contextualized model capable of strengthening religious integrity, economic resilience, intellectual maturity, environmental awareness, and intergenerational continuity within Muslim communities. The ASyA Theory thus presents a transformative approach that shifts maqasid from a purely normative framework into an operational strategy for social resilience. It is proposed as a foundational model for future empirical research, educational reform, and policy-oriented Islamic social development.